2021
DOI: 10.1038/s41698-021-00146-7
|View full text |Cite
|
Sign up to set email alerts
|

Rare deleterious germline variants and risk of lung cancer

Abstract: Recent studies suggest that rare variants exhibit stronger effect sizes and might play a crucial role in the etiology of lung cancers (LC). Whole exome plus targeted sequencing of germline DNA was performed on 1045 LC cases and 885 controls in the discovery set. To unveil the inherited causal variants, we focused on rare and predicted deleterious variants and small indels enriched in cases or controls. Promising candidates were further validated in a series of 26,803 LCs and 555,107 controls. During discovery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…Haplotype studies indicate that light or heavy smoking conferred high risk, demonstrating that the individuals in these families are particularly sensitive to tobacco exposure. Rare deleterious cancer risk variants have also been described recently to significantly impact lung cancer risk ( 4 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Haplotype studies indicate that light or heavy smoking conferred high risk, demonstrating that the individuals in these families are particularly sensitive to tobacco exposure. Rare deleterious cancer risk variants have also been described recently to significantly impact lung cancer risk ( 4 ).…”
mentioning
confidence: 99%
“…Rare deleterious cancer risk variants have also been described recently to significantly impact lung cancer risk. [4] As for common genetic variants and lung cancer risk, the region identified in early GWAS studies included a neuronal nicotinic acetylcholine receptor gene cluster comprising cholinergic receptor nicotine alpha 5 CHRNA5, CHRNA3, and CHRNB4 subunits. Since the 2008 studies, 51 susceptibility loci have been found for lung cancer among a variety of populations and ethnicities, each one accounting for small to moderate proportion of risk, in smokers.…”
mentioning
confidence: 99%
“…However, we speculate that most of these VUS were detected in cancer patients may be supportive of their pathogenic potential. That's the reason of why all the most recent studies are focusing on the effects of rare variants that are hardly classified not only in cancer but also in rare diseases such as immunodeficiencies [ [17] , [18] , [19] ]. Even the VUSs have no functional studies supporting their pathogenicity, this study may provide as the first case series covering the all Turkey and a sourceful data for future functional studies or case based reportings and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is not limited to breast cancer, but is progressively being studied across different cancer typessee, e.g. recent work on ovarian [Kanchi et al, 2014, Phelan et al, 2017, George et al, 2021 skin [Goldstein et al, 2017], pancreatic [Zhan et al, 2018], prostate [Nguyen-Dumont et al, 2020], lung [Liu et al, 2021] cancer). In downstream analysis, this estimates could be useful for planning and design of future experiments, e.g.…”
Section: Predicting the Number Of New Rare Genetic Variants In Cancer...mentioning
confidence: 99%